The age and paleoclimate implications of relict periglacial block deposits on the New England Tablelands, Australia. (January 2023) - Slee, Adrian; Barrows, Timothy T.; Shulmeister, James; Gontz, Allen; Kiernan, Kevin; Haworth, Robert; Clark, Douglas; Fifield, L. Keith
Abstract: Pleistocene periglacial activity in eastern Australia was widespread and has been predicted to have extended along much of the east coast. This paper describes block deposits in the New England Tablelands, Australia, as far north as 30°S. These deposits are characterized by openwork blocks on slopes below the angle of repose. The deposits are positioned where frost cracking was significant and range in area up to 8 ha. Surface exposure dating using the cosmogenic nuclide 36 Cl from four block deposits indicate all sites were active late during the last glacial cycle, with a concentration of activity between 15–30 ka. Modern temperature measurements from block deposits highlight the importance of local topography for promoting freezing. Periglacial deposits are likely to have been more extensive than previously recognized at these northern limits, and mean annual temperature more than 8°C colder than today.